The Routledge international handbook of clinical hypnosis - Linden, Julie Hope; Sugarman, Laurence I.; De Benedittis, Giuseppe (Associate professor of neurosurgery); Varga, Katalin (Psychology professor) (New York, NY : Routledge, 2024)
"The Routledge International Handbook of Clinical Hypnosis explores and clarifies the challenge of defining what hypnosis is and how best to integrate it into treatment. It contains state of the art neuroscience, cutting edge practice, and future-oriented visions of clinical hypnosis integrated into all aspects of health and clinical care. Chapters gather current research, theories, and applications in order to view clinical hypnosis through the lens of neurobiological plasticity and reveal the central role of hypnosis in healthcare. This handbook catalogues the utility of clinical hypnosis as a biopsychosocial intervention amid a broad range of treatment modalities and contexts. It features contributions from esteemed international contributors, covering topics such as: self-hypnosis, key theories of hypnosis, hypnosis and trauma, hypnosis and chronic pain management, attachment, and more. This handbook is essential for researchers, clinicians, and newcomers to clinical hypnosis, in medical schools, hospitals, and other healthcare settings"--
Keywords: Hypnotism; PSYCHOLOGY / Mental Health